THE CATEGORY OF POLITENESS AS AN OBJECT OF INTERDISCIPLINARY STUDY - Qaypova, Bibiruza Kalbaevna (SCIENCE and SOCIETY, 2026)
The article examines the category of politeness as one of the central categories in human communication, as well as a linguistic, social, and cultural mechanism that regulates interpersonal relationships and ensures social harmony. This research examines politeness from the perspective of various disciplines such as pragmatics, ethnolinguistics, and sociolinguistics, analyzing the ethical strategies of context, cultural norms, and social hierarchy.
Keywords: politeness; linguistics; pragmatics; ethnolinguistics; sociolinguistics; intercultural communication